التربية الاسلامية و قضية النحياز في المدارس الاسلامية (دراسة حالة في 20 مدرسة بجاوي) - Iklilah Muzayyanah Dini Fajriah (Millah: Journal of Religious Studies, 2012)
This article is summary of qualitative research in the perspective of gender which is conducted in 20 Islamic schools (madrasah) spread across the island of Java. The study focuses on issues of gender bias that occurs in primary and secondary education, especially those occur in the environment of Islamic school (Madrasah) as an educational institution that has Islamic characteristic. From critical analysis of the literatures and a result of field research, it proved that gender bias education resulted in disadvantage not only for women, but also men in the macro scale. While a just education in gender proved to have positive impact on every element of society. More specifically, it is known from field findings in this research that gender bias practices not only occur in the process of learning in the Islamic school sphere, but also in the source of learning routine activities of Islamic school (madrasah), extracurricular activities, even those related to small-scale policy in the level of educational unit.